Effect of PolyPhosphoric Acid on Rutting Resistance of Asphalt Concrete Mixture - Hussein Burhan Raof; Mohammed Qadir Ismael (Salehan Institute of Higher Education, 2019)
The action of high repeated trucks load associated with dramatically elevated ambient temperatures leads to the most harmful distress in asphalt pavements occurred in Iraq known as rutting. Essentially, it is produced from the accumulation of irrecoverable strains, which mainly occurred in the asphalt layers. That visually demonstrated as a longitudinal depression in the wheel paths as well as small upheavals to the sides. Poly Phosphoric Acid (PPA) has been used as a means of producing modified asphalt binders and the interest to use it has increased in recent years. The PPA provides modified asphalt binder, which is relatively cheaply produced compared to polymer-modified asphalt. In this paper, PPA was used by three-percentages 1, 2 and 3 % of the weight of asphalt binder. Two asphalt binder grades were used in this study, 40-50 and 60 -70. The evaluation process based on conducting Marshall Test, Compressive strength test and the Wheel Tracking test. The optimum asphalt content was determined for eight asphalt mixture. The results of the index of retained strength of modified asphalt were slightly increased compared with conventional mixtures. The rut depth was determined by using wheel tracking device at different temperature (45 and 55 ºC) for each asphalt mixture under 10000 cycles and the results showed that modified asphalt with PPA produced mixtures with more rutting resistance than conventional asphalt mixture. Moreover, the effect of PPA on rutting resistance for asphalt grade 60-70 was higher than asphalt grade 40-50.